Devoted Resistance : Jewish Feminist Art in the US and Israel - Sperber, David, (Jews, Judaism, and the Arts ;, 2025)
What is Jewish-feminist art, and how does it contribute to the spaces of art, society, and religion? Devoted Resistance examines the nature, methods of operation, and contribution of the feminist art movement, which has developed in traditional Jewish spheres since the late 1990s in the two major Jewish centers - the United States and Israel. The book analyzes critical Jewish feminist art and the different fields in which it operates; it explores the interrelationships between feminist Jewish art and feminist theories; the connection between critical discourse and feminist activism in observant Jewish worlds; and feminist artists and artwork in these spaces. Devoted Resistance highlights aspects common to feminist Jewish artists who create from traditional spheres and amalgamate the "social" with the "theological," connecting private experience with community existence. It offers new and vital contextual understandings regarding the relationship between feminist art and Jewish Identity, illuminating their relationship through Jewish religion rather than merely Jewish ethnicity. By doing so, the book demonstrates how art, theology, feminism, and critical thinking interwind.